2005
DOI: 10.1016/j.aquaculture.2005.04.075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, salinity and pH on larval growth, survival and development of the sea cucumber Holothuria spinifera Theel

Abstract: For large-scale seed production of sea cucumbers through a hatchery system, it is imperative to know the effects of environmental parameters on larval rearing. Auricularia larvae (48 h post-fertilization) were obtained from induced spawning of Holothuria spinifera and used in experiments to ascertain the effects of temperature, salinity and pH on the growth and survivorship of the larvae. The larvae were reared for 12 days at temperatures of 20, 25, 28 and 32 8C; salinities of 15, 20, 25, 30, 35 and 40 ppt; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 2 publications
3
61
0
1
Order By: Relevance
“…Whereas, in the December 2016, Paracaudina australis samples were collected at the full moon. This does not fit with the researchs that showed most of the sea cucumber such as Holuthuria spinifera, Holothuria scabra and Cucumaria frondosa have spawing in the new moon (Conand, 1993;Hamel and Mercier, 1995;Asha and Muthiah, 2005). In the temperate region, most of sea cucumber have spawning time in spring and summer (Hamer et al, 1993), while in (Conand, 1993).…”
Section: Gonad Maturity Stagementioning
confidence: 81%
“…Whereas, in the December 2016, Paracaudina australis samples were collected at the full moon. This does not fit with the researchs that showed most of the sea cucumber such as Holuthuria spinifera, Holothuria scabra and Cucumaria frondosa have spawing in the new moon (Conand, 1993;Hamel and Mercier, 1995;Asha and Muthiah, 2005). In the temperate region, most of sea cucumber have spawning time in spring and summer (Hamer et al, 1993), while in (Conand, 1993).…”
Section: Gonad Maturity Stagementioning
confidence: 81%
“…The previous studies reported that optimal temperature for growth is species-specific and in consistent to this study, feeding activity reduced outside temperature tolerance range. In several studies, optimumtemperature for tropical species as Holothuria atra and Holothuria scabra were reported over 20°C (Seeruttun et al, 2007;Lavitra et al, 2010) while optimum temperature for cold water species as Apostichopus japonicus and Stichopus japonicas were reported below 20°C as 15-18°C for Apostichopus japonicus (Yu and Song, 1999;Asha and Muthiah, 2005) and 5-15°C for Stichopus japonicus (Chen, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…tubulosa as a deposit-feeder, ingests superficial sediment, feed on non-living detritus and associated microorganisms (Massin and Jangoux, 1976, Moriarty, 1982, Birkeland, 1988 and inhabits Posidonia oceanica meadows where it often occurs in dense populations and represents a significant part of the macrozoobenthic biomass of the Mediterranean Sea (Mezali, et al, 2006;Costa et al, 2014). Most aspidochirotid holothurians follow the life cycle of pre-auricularia, early, mid and late auricularia and subsequent metamorphosis to the doliolaria (nonfeeding) stage before settlement, pentactula, juvenile and adult stages (Hamel and Mercier, 1996;Hamel et al, 2003;Laxminarayana, 2005;Asha and Muthiah, 2002;Asha and Muthiah, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They have been selected for this study because they are osmoconformer organisms, and 15 therefore they are not able to regulate their osmotic pressure [11], and several studies have shown that these organisms can tolerate only a narrow range of salinities [17,18]. Salinity also may play a vital role in echinoderms larval development [19]. Our results sug-20 gest that high salinity diminishes echinoderms density in affected areas, but we cannot conclude whether the high salinities have produced an increment in the mortality of these species or induced its displacement to other areas outside the influence of the brine.…”
Section: Discussionmentioning
confidence: 99%